De mercadorias e oferendas : etnografia das práticas econômicas nos ritos e festas de religiões afro-gaúchas - Rossoni, Bibiana (2019)
From a participant observation of parties and rites of afro-gauchas religions in two temples in Porto Alegre I present an ethnography of the economic practices of their followers. I seek to analyze how happens the management of financial resources and people to rituals. The African origins religions have their ethos based on the “logic of the gift”, on circulation of divine energy and on values of solidarity and care for the maintenance of “Axé”. Gifts and rituals renew the bond with deity, maintaining the basis of the relationship with the holy and sustaining the "Axé". To ensure “effectiveness” of rituals, in addition to knowing the religious foundations, purchases should be made from suppliers that guarantee the origin of materials. However, to become gifts, these goods depend on the “hand”, the strength of the priest's “Axé” turning them into the magical elements of a ritual.